2020
DOI: 10.1021/acsomega.0c01689
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Protects Mice against Methionine–Choline-Deficient-Diet-Induced Nonalcoholic Steatohepatitis by Improving Gut Microbiota To Attenuate Hepatic Injury and Regulate Metabolism

Abstract: Epigallocatechin gallate (EGCG) has been regarded as a protective bioactive polyphenol in green tea against nonalcoholic steatohepatitis (NASH), but the mechanism remains poorly deciphered. Herein, we assessed the role and mechanism of EGCG on gut microbiota and the metabolism in NASH development. Forty-eight male C57BL/6J mice were fed with either a methionine–choline-sufficient diet or a methionine–choline-deficient (MCD) diet with or without EGCG administration for 4 weeks. Liver injury, inflammation, lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 56 publications
3
28
1
Order By: Relevance
“…It is important to consider the effects of EGCG on carbohydrate metabolism, as carbohydrate accumulation has detrimental effects on obesity and liver disease. Interestingly, all studies addressing the impact of EGCG on carbohydrate metabolism reported significant decreases in glucose and insulin levels, as well as insulin resistance (IR), with EGCG treatment [ 11 , 12 , 14 , 15 , 16 , 17 , 23 , 24 , 25 , 26 , 27 , 33 , 34 , 35 , 36 , 37 ] ( Table 1 ). Gan et al showed in their study that intraperitoneal administration of EGCG dose-dependently alleviates hyperinsulinemia, hyperglycemia, and IR [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider the effects of EGCG on carbohydrate metabolism, as carbohydrate accumulation has detrimental effects on obesity and liver disease. Interestingly, all studies addressing the impact of EGCG on carbohydrate metabolism reported significant decreases in glucose and insulin levels, as well as insulin resistance (IR), with EGCG treatment [ 11 , 12 , 14 , 15 , 16 , 17 , 23 , 24 , 25 , 26 , 27 , 33 , 34 , 35 , 36 , 37 ] ( Table 1 ). Gan et al showed in their study that intraperitoneal administration of EGCG dose-dependently alleviates hyperinsulinemia, hyperglycemia, and IR [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…EGCG treatment also improves liver damage biomarkers [ 10 , 11 , 12 , 14 , 16 , 17 , 19 , 24 , 27 , 28 , 29 , 30 , 32 , 34 , 35 , 36 , 37 , 38 ]. As shown in Table 1 , EGCG decreases levels of enzymes associated with liver damage, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP).…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis, a newly identified type of “programmed necrosis” characterized by lipid peroxidation in an iron-dependent manner ( Dixon et al, 2012 ; Chen et al, 2020 ), has been confirmed to be involved in the pathological processes of various diseases ( Fang et al, 2019 ; Martin-Sanchez et al, 2020 ; Mahoney-Sanchez et al, 2021 ). Recently, ferroptosis was proven to affect the progression of NASH by modulating lipid peroxidation in a methionine/choline-deficient diet-induced NASH mouse model ( Ning et al, 2020 ). Previous studies have reported that Que has the ability to alleviate pancreatic β cell injury in type 2 diabetes and acute kidney injury by inhibiting ferroptosis ( Li D. et al, 2020 ; Wang et al, 2021 ), but whether Que can inhibit ferroptosis to improve NAFLD has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, they noticed that each treatment had a different effect on the gut microbiota, suggesting that the benefits observed in the liver were not, at least entirely, dependent on the gut microbiota [ 69 ]. Conversely, Ning et al [ 70 ] suggested that shifts caused in gut microbiome by EGCG could be related to benefits against nonalcoholic steatohepatitis. They fed C57BL/6J mice with EGCG, observing a change in the microbial community similar to those described before and characterized by a decrease in Firmicutes and an increase in Bacteroidetes .…”
Section: Influence Of Green Tea On Health Via Gut Microbiotamentioning
confidence: 99%
“…They fed C57BL/6J mice with EGCG, observing a change in the microbial community similar to those described before and characterized by a decrease in Firmicutes and an increase in Bacteroidetes . Additionally, they found that several enzymes implicated in lipid accumulation were expressed in lower abundance when mice were fed with EGCG [ 70 ]. These authors therefore suggested a potential benefit against liver disease, though they acknowledged that more research was needed since results were not definitive.…”
Section: Influence Of Green Tea On Health Via Gut Microbiotamentioning
confidence: 99%